Investigation of the mechanical properties of corroded sintered silver layers by using Nanoindentation. (November 2020) - Kolbinger, E.; Kuttler, S.; Wagner, S.; Schneider-Ramelow, M.
Abstract: The aim of this study is to gain a better understanding of the behaviour of sintered silver layers for e.g. power electronic applications in corrosive environments. It explicitly deals with the influence of corrosion products on the mechanical properties using Nanoindentation measurements. In addition to these measurements, analytical investigations and porosity analyses are performed. Existing studies mainly deal with the investigation of unaged sintered silver layers or the influence of thermomechanical ageing on the mechanical properties. In contrast, this study focuses on the investigation of the influence of corrosion on the mechanical properties of sintered silver layers. The results show that an increased Young's modulus can be detected by Nanoindentation measurements on corrosion-stressed highly porous sintered silver. In addition, increased indentation hardness is also determined. Besides the already known influences on the Young's modulus, a significant influence on the corrosion pattern of the sintered silver layers can be shown. The results are discussed with regard to a filled pore system of the samples. Highlights: Electrochemical measurements and Nanoindentation enable investigation of mechanical properties of corroded sintered silver. The corrosion of highly porous sintered silver layers causes an increase in the Young's modulus and indentation hardness. The change in mechanical properties can be primarily attributed to the filling of the pores by the corrosion product. The effect of the change in mechanical properties is not as pronounced in low porosity sintered silver layers.